Integration or separation? Spatial and temporal representations of whole-body movements in visual working memory. - Chiou, Shiau-Chuen (Memory & Cognition, 2023)
Spatial and temporal information are two major feature dimensions of human movements. How these two types of information are represented in working memory—whether as integrated units or as individual features—influences how much information might be retained and how the retained information might be manipulated. In this study, we investigated how spatial (path/trajectory) and temporal (speed/rhythm) information of complex whole-body movements are represented in working memory under a more ecologically valid condition wherein the spatiotemporal continuity of movement sequences was considered. We found that the spatial and temporal information are not automatically integrated but share the storage capacity and compete for a common pool of cognitive resources. The finding rejects the strong form of object-based representation and supports the partial independence of spatial and temporal processing. Nevertheless, we also found that contextual factors, such as the way movements are organized and displayed, can further modulate the level of object-based representation and spatiotemporal integration.